Efeito do gerenciamento de resultados e do excesso de confiança no desempenho econômico das adquirentes em fusões e aquisições - Bispo, Oscar Neto de Almeida (2019)
This thesis aimed to verify the effect of earnings management and overconfidence on the economic performance of acquirer companies in mergers and acquisitions in Brazil. Specifically, the study aimed to: (i) verify whether acquirers raise accruals and real activities earnings management levels in the year before mergers and acquisitions; (ii) verify the effect of overconfidence and accruals and real activities earnings management on the probability of mergers and acquisitions occurrence; and (iii) evaluate whether post mergers and acquisitions economic performance, of the acquirers, can be explained due to overconfidence and earnings management by accruals and real activities.The study object comprised 31 mergers and acquisitions in Brazil between 2008 and 2014.The data treatment and analysis used multiple regression and logistic regression techniques, and means and medians difference analysis. The results obtained, in general, indicated that means and medians of the proxy by accruals earnings management are different between acquiring and non-acquiring companies in the year beforemerges and acquisitions. However, the same result has not been when considering the proxies of earnings management by real activities. When compared acquirers and non-acquirers, the accruals earnings management proxy has been, on average, higher in acquirers in the year preceding merger and acquisition transactions. For the proxies by earnings management real activities, on average, only the abnormal cash flow has been higher in the acquirers during the same period. The findings do not support any inference about abnormal production costs and abnormal general, sales and administrative expenses, given that these variables were not statistically significant on the econometric regressions used. Thus, regarding the trade-off between earnings management strategies, by accruals or real activities, the acquirers were more inclined to use accruals earnings management and abnormal recognition of operational cash flow in the year preceding mergers and acquisitions. About the understanding of the effect of overconfidence and earnings management by accruals and real activities on the probability of mergers and acquisitions occurrence, the results pointed out that only the earnings management proxy by accruals has a positive influence on the probability of a company become an acquirer. Finally, when evaluated whether post mergers and acquisitions economic performance, of the acquirers, could be explained due to overconfidence and earnings management by accruals and real activities, the study found no relation, either jointly or separately, between these variables and future economic performance. Thus, responding to the proposed research problem, the results did not find evidence to affirm that earnings management and overconfidence affect the economic performance of the acquirers in mergers and acquisitions in Brazil.